2022
DOI: 10.3390/su14094933
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of Climatic and Land Use Changes on Habitat Suitability and Protected Area Adequacy across the Asian Elephant’s Range

Abstract: Climate change and human activities have caused dramatic impacts on biodiversity. Although a number of international agreements or initiatives have been launched to mitigate the biodiversity loss, the erosion of terrestrial biome habitats is inevitable. Consequently, the identification of potential suitable habitats under climate change and human disturbance has become an urgent task of biodiversity conservation. In this study, we used the maximum entropy model (MaxEnt) to identify the current and potential fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
1
0
0
Order By: Relevance
“…Based on the simulation results from the three past periods, it can be observed that both M. kokonorica and M. chinensis have exhibited trends of not only northward migration to higher latitude but also westward migration along the Himalayas to higher elevations. This observation is consistent with the findings of most studies on suitable habitats (Anand et al., 2021 ; Yan et al., 2021 ; Yang et al., 2022 ). Comparing the simulation results of potentially suitable areas between the current and future periods, there was little change in total suitable areas for M. kokonorica .…”
Section: Discussionsupporting
confidence: 92%
“…Based on the simulation results from the three past periods, it can be observed that both M. kokonorica and M. chinensis have exhibited trends of not only northward migration to higher latitude but also westward migration along the Himalayas to higher elevations. This observation is consistent with the findings of most studies on suitable habitats (Anand et al., 2021 ; Yan et al., 2021 ; Yang et al., 2022 ). Comparing the simulation results of potentially suitable areas between the current and future periods, there was little change in total suitable areas for M. kokonorica .…”
Section: Discussionsupporting
confidence: 92%
“…We show that both the GLTFCA and LTFCA have been linked by trailblazing bulls with this connectivity involving two South African national parks (KNP and Tembe Elephant Park) and five PAs within Eswatini (Big Bend Conservancy, Hlane Royal National Park, Mkhaya Game Reserve, Mlawula Nature Reserve and Panata Ranch) over an international border and across three political borders (South Africa, Eswatini and Mozambique). The next step will be to model the occurrence of elephant locations versus suitable habitat (see [70]). This is being carried out in a follow up study (Bedetti et al in prep.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the geopolitical situation since the start of the Russo-Ukrainian war further hinders joint action on climate change issues [79]. Although both scenarios involve high greenhouse gas emissions, they provide a basis for studying the impacts of climate change on agriculture and the natural environment [76,[80][81][82][83][84]. The time frames involve the 1981-2010 reference period and the 2011-2040, 2041-2070 and 2071-2100 periods designated, respectively, as Ref, p1, p2 and p3.…”
Section: Methodsmentioning
confidence: 99%